Peran Drama untuk Siswa Sekolah Dasar - Riris Setyasa Hermawati; Olyvia Hera Anggreana; Nafisa Amelia; Bintang Oktaviana; Artika Chrissa Agustina; Bayu Purbha Sakti (CV. ITTC INDONESIA, 2025)
This paper examines the role and benefits of drama as a learning method in elementary schools. Drama is not only a form of literary work performed, but also serves as an effective medium for developing various student abilities, including cognitive, affective, social, and psychomotor aspects. In the learning process, drama can improve speaking skills, self-confidence, empathy, and the ability to cooperate among students. This study uses a literature review method by examining various literature sources related to education, drama learning, and its application to elementary school children. In addition, this paper also discusses various types of drama in general and drama that is suitable to be introduced to elementary school students, such as folk theater and pantomime. By utilizing drama, learning becomes more interesting and enjoyable and supports the overall development of students. Therefore, the use of drama in elementary education is very important to help shape character and improve the quality of student learning.